Expression of Sirtuins in the Retinal Neurons of Mice, Rats, and Humans - Luo, Hongdou; Zhou, Min; Ji, Kaibao; Zhuang, Jiejie; Dang, Wenjie; Fu, Shiya; Sun, Tao; Zhang, Xu (Frontiers in Aging Neuroscience, 2017)
Sirtuins are a class of histone deacetylases (HDACs) that have been shown to regulate a range of pathophysiological processes such as cellular aging, inflammation, metabolism, and cell proliferation. There are seven mammalian Sirtuins (SIRT1-7) that play important roles in stress response, aging, and neurodegenerative diseases. However, the location and function of Sirtuins in neurons are not well defined. This study assessed the retinal expression of Sirtuins in mice, rats, and humans and measured the expression of Sirtuins in aged and injured retinas. Expression of all 7 Sirtuins was confirmed by Western blot and Real-Time PCR analysis in all three species. SIRT1 is highly expressed in mouse, rat, and human retinas, whereas SIRT2-7 expression was relatively lower in human retinas. Immunofluorescence was also used to examine the expression and localization of Sirtuins in rat retinal neurons. Importantly, we demonstrate a marked reduction of SIRT1 expression in aged retinal neurons as well as retinas injured by acute ischemia-reperfusion. On the other hand, none of the other Sirtuins exhibit any significant age-related changes in expression except for SIRT5, which was significantly higher in the retinas of adults compared to both young and aged rats. Our work presents the first composite analysis of Sirtuins in the retinal neurons of mice, rats, and humans, and suggests that increasing the expression and activity of SIRT1 may be beneficial for the treatment of glaucoma and other age-related eye dysfunction.